1980
DOI: 10.1002/1097-0142(19800501)45:9<2330::aid-cncr2820450916>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco-induced changes in oral leukoplakic epithelium

Abstract: A study of 112 biopsy specimens from Danish oral leukoplakia patients and 145 biopsy specimens from Indian leukoplakia patients revealed a chevron-like keratinization of the epithelium in a number of cases. Clinically, this type of keratinization was often characterized by a pumice-like appearance. The clinical and histologic changes were only observed in tobacco users, and appeared to be associated particularly with use of pipes, snuff, and hooklis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(25 citation statements)
references
References 15 publications
0
24
1
Order By: Relevance
“…Currently, Giemsa stains are also widely used in micronuclei studies with nonepithelial cells originating from a number of organs, e.g., in experiments with polychromatic erythrocytes in bone marrow of rodents (44), lymphocytes (45), splenocytes (46), and liver cells (47), and in in vitro studies with stable cell lines (48). Because the formation of keratin bodies and of the nuclear anomalies described above are an adaptive response to cell damage, which is only seen in (normally nonkeratinizing) epithelial cells (49,50), it is likely that the overestimation of micronuclei formation with nonspecific stains is only relevant for experiments with epithelial cells, e.g., from the oral cavity, cervix, bladder, and esophagus. This assumption is supported by the findings of Surrales et al (51), who compared micronuclei frequencies in human lymphocytes stained with DAPI and Giemsa and found even higher frequencies with the former stain.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Giemsa stains are also widely used in micronuclei studies with nonepithelial cells originating from a number of organs, e.g., in experiments with polychromatic erythrocytes in bone marrow of rodents (44), lymphocytes (45), splenocytes (46), and liver cells (47), and in in vitro studies with stable cell lines (48). Because the formation of keratin bodies and of the nuclear anomalies described above are an adaptive response to cell damage, which is only seen in (normally nonkeratinizing) epithelial cells (49,50), it is likely that the overestimation of micronuclei formation with nonspecific stains is only relevant for experiments with epithelial cells, e.g., from the oral cavity, cervix, bladder, and esophagus. This assumption is supported by the findings of Surrales et al (51), who compared micronuclei frequencies in human lymphocytes stained with DAPI and Giemsa and found even higher frequencies with the former stain.…”
Section: Discussionmentioning
confidence: 99%
“…The use of smokeless tobacco has been associated with various abnormalities of the oral mucosa including hyperkeratotic or erythroplakic lesions, periodontal inflammation, cervical erosion of the teeth, and oral cancer [Pindborg et al, 1980;Greer and Poulson, 1983;Jungell and Malmstrom, 1985;Landy and White, 1961;Vogler et al, 1962;Rosenfeld and Callaway, 1963;Brown et al, 1965;Winn et a]., 198 I]. An Advisory Committee to the Surgeon General and the International Agency for Research on Cancer reported that oral use of smokeless tobacco represented a significant health risk [U.S. Dept.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding it is to note that the micronuclei frequency as well as the frequency of karyorrhexis, and broken eggs in our exposed group was statistically higher than the micronuclei frequency in the control group. The presence of broken eggs is an anomaly not well studied, perhaps related to cytogenetic damage, while karyorrhexis is an event accompanying the apoptotic processes which are under genetic control, and its greater frequency in the buccal cells of these workers, may indicate an adverse cellular reaction or a mechanism provided to eliminate cells with genetic damage (Tolbert et al 1992;Pindborg et al 1980;Wyllie 1981).…”
Section: Discussionmentioning
confidence: 99%